Optical fiber sensor measuring instrument and signal conditioning / Khairul Azman Ahmad - Ahmad, Khairul Azman (1999)
Optical fiber sensor measuring instrument has been developed to detect color variation and micrometer displacement. Many applications can be derived from the measurements. The use of a single core optical fiber cable is an advantage in order to extend the length of transmission signal, compared to the previous projects. The additional switch has been added to select the red LED or blue LED for various applications. The selection LED is depended on the reaction of chemical pesticide in vegetables or firuits. Red oxide is only reacted with red light. The instrument employed opto-electronics devices such as light emittmg diodes as a light source and semiconductor photodiodes as a photodetector. Signal amplification and conditioning has been developed to interface the instrument with panel meter and computer. The instrument uses regulated power supplies +/-12 V and 0 to +5 V. Promising results for colors and displacements measurement have been obtained.